Evaluate: 2-5(x+5)=3(x-2)-1

Expression: $2-5\left( x+5 \right)=3\left( x-2 \right)-1$

Distribute $-5$ through the parentheses

$2-5x-25=3\left( x-2 \right)-1$

Distribute $3$ through the parentheses

$2-5x-25=3x-6-1$

Calculate the difference

$-23-5x=3x-6-1$

Calculate the difference

$-23-5x=3x-7$

Move the variable to the left-hand side and change its sign

$-23-5x-3x=-7$

Move the constant to the right-hand side and change its sign

$-5x-3x=-7+23$

Collect like terms

$-8x=-7+23$

Calculate the sum

$-8x=16$

Divide both sides of the equation by $-8$

$x=-2$